Sperm Fertility of SK Kedu Chicken in Lactated Ringer’s-Egg Yolk Extender with 10% of DMSO - Sipora Petronela Telnoni Nella (International Journal of Applied Biology, 2021)
This study was conducted to evaluate fertility of SK Kedu chicken post inseminated by frozen semen using lactated ringer’s-egg yolk with 10% of DMSO. Frozen semen of lactated ringer’s-egg yolk with 10% of DMSO was picked from container of Liquid Nitrogen (-196 ºC) and thawed in warm water at 37 ºC for 30 second. Frozen semen inseminated to 3 arab hens: A1, A2 and A3 with 100 motile sperm cell in 0.25 mL-1 using 2 straws and deposited into reproductive tract of hen as long as 7 cm in intra utein using AI gun. Egg was collected in day 2 after AI till day 14, labelled and incubated. Sperm fertility was estimated by using % sperm fertility formulation = fertile eggs / incubated eggs x 100, regardless of whether the eggs will hatch or not. Egg fertility are checked on 5 day after incubation. This result showed % sperm fertility of SK kedu chicken were A1 (77.78 %), A2 (33.33 %), and A3 (83.33 %). The mean of % sperm fertility was 72.22 %. It can be concluded that lactated ringer’s-egg yolk with 10% of DMSO can maintain sperm fertility of SK kedu chicken.